The New Key of Competitive Advantage in Business - Dana Adriana Lupșa-Tătaru (Ovidius University Annals: Economic Sciences Series, 2019)
Given the new knowledge economy, competitive environment, the rise of the new technologies and also the new instruments for marketing and management – from social media to software, from chatbots to ERP – every business has to understand that adjusting to the new conditions is vital not only to survive, but to have a competitive advantage. Using the new strategies and trends for communication is actually the key of a business development and the key to competitive advantage. In this paper, the author explores the nature of a communication strategy in the context of social media, briefly summarize the process followed in developing a communication strategy for a small business and share lessons learned useful to others involved in strategic planning efforts.